Plate-Based Respirometry to Assess Thermal Sensitivity of Zebrafish Embryo Bioenergetics in situ - Rollwitz, Erik; Jastroch, Martin (Frontiers in Physiology, 2021)
Oxygen consumption allows measuring the metabolic activity of organisms. Here, we adopted the multi-well plate-based respirometry of the extracellular flux analyzer (Seahorse XF96) to investigate the effect of temperature on the bioenergetics of zebrafish embryos (Danio rerio) in situ. We show that the removal of the embryonal chorion is beneficial for oxygen consumption rates (OCR) and penetration of various mitochondrial inhibitors, and confirm that sedation reduces the variability of OCR. At 48 hours post-fertilization, embryos (maintained at routine temperatures of 28°C) were exposed to different medium temperatures ranging from 18°C to 37°C for 20 hours prior OCR measurement. Measurement temperatures from 18°C to 45°C in the XF96 were achieved by lowering environmental temperature and active in-built heating. At 18°C assay temperature, basal OCR was low due to decreased ATP-linked respiration, which was not limited by mitochondrial power, as seen in substantial spare respiratory capacity. Basal OCRs of the embryos increased with assay temperature and were stable up to 37°C assay temperature, with pre-exposure of 37°C resulting in more thermoresistant basal OCR measured at 41°C. Adverse effects of the mitochondrial inhibitor oligomycin were seen at 37°C and chemical uncouplers disrupted substrate oxidation gradually with increasing assay temperature. Proton leak respiration increased at assay temperatures above 28°C and compromised the efficiency of ATP production, calculated as coupling efficiency. Thus, temperature impacts mitochondrial respiration by reduced cellular ATP turnover at lower temperatures and by increased proton leak at higher temperatures. This conclusion is coherent with the assessment of heart rate, an independent indicator of systemic metabolic rate, which increased with exposure temperature, peaking at 28°C, and decreased at higher temperatures. Collectively, plate-based respirometry allows assessing distinct parts of mitochondrial energy transduction in zebrafish embryos, and investigating the effect of temperature and temperature acclimation on mitochondrial bioenergetics in situ.